TRANSFORMASI BISNIS DI ERA DIGITAL MELALUI LITERASI ENTREPRENEUR SEBAGAI PENDEKATAN ISLAMI DALAM PENDIDIKAN AGAMA ISLAM - Lutfi Lutfi; Maftuhah Maftuhah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2024)
The development of business in the digital era brings new opportunities and challenges in the world of education, including Islamic Religious Education (PAI). This article discusses the importance of entrepreneurial literacy as an Islamic approach to responding to changes in the digital era. Entrepreneurial literacy in this context refers to the understanding and mastery of entrepreneurial skills based on Islamic values, such as honesty, responsibility, and usefulness to society. This approach is designed to equip students with the ability to adapt to technological changes while implementing business ethics according to Islamic teachings. This study uses a qualitative method with a descriptive-analytical approach. Data were obtained through literature studies, field observations, and interviews with educators and business actors who implement Islamic values. The results of the study revealed that the integration of entrepreneurial literacy in PAI can change students' perspectives, from being passive users of technology to being innovators and productive business actors. In addition, this approach makes PAI more relevant to the needs of the times and helps strengthen students' Islamic character amidst the challenges of the modern era. This study recommends the preparation of an PAI curriculum that includes entrepreneurial literacy as a main component. The successful implementation of this approach also requires synergy between educators, business actors, and educational institutions. Thus, PAI not only functions as spiritual guidance, but also as a driver of social and economic transformation based on Islamic values ​​in the digital era.